Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Dodol Piaraja: - Amar Adly; Fitri Handayani Sitorus Pane; Arinah Syahira; Febby Ayu Syahputri Gurning; Yolanda Sambas (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Marketing strategy is one of the important points in achieving competitive advantage on an ongoing basic. To support a business to progress, proper and effective planning is needed as a guide for communiti work units in carrying out their activities. In addition, the existence of tight competition in the business world is also a strong reason for the need for a marketing strategy. Thes study aims to evaluate the marketing strategy applied and determine the level of effectiveness of the application of the marketing strategy in increasing sales of Piaraja dodol in Marunjuk Aceh Village. The research method used is a qualitative descriptive method where the data are taken from the results of surveys and interviews. The results of this study are the strategies used by business actors in marketing dodol piaraja, namely the formulation of marketing strategies starting from the strategy of determining marketing targets (targeting), and market positioning strategies (positioning). In addition, business actors also develop their marketing strategies by implementing a marketing mix strategy. From the results of the analysis, also stated the marketing strategy applied by business actors is quite effective.